Missing the piano - Rapp, Adam. (New York, N.Y., U.S.A. : Viking, 1994)
When Mike's mother and sister go on tour with "Les Miserables," Mike's father and his new wife enroll Mike in St. Matthew's Military Academy where, facing brutality and ignorance, he learns to survive.
Keywords: Military education -- Fiction; Boarding schools -- Fiction; Schools -- Fiction; Family problems -- Fiction; Coming of age -- Fiction